Visuospatial Deficits Predict Rate of Cognitive Decline in Autopsy-Verified Dementia with Lewy Bodies - Hamilton, Joanne M. (2008)
Dementia with Lewy Bodies (DLB) is often characterized by pronounced impairment in visuospatial skills, attention, and executive functions. However, the strength of the phenotypic expression of DLB varies and may be weaker in patients with extensive concomitant Alzheimer’s disease (AD). To determine whether strength of the DLB clinical phenotype impacts cognitive decline, visuospatial and language tests were retrospectively used to predict two-year rate of global cognitive decline in 22 autopsy-confirmed DLB patients (21 with concomitant AD) and 44 autopsy-confirmed “pure” AD patients. Generalized Estimating Equations (GEE) revealed a significant interaction such that poor baseline performances on tests of visuospatial skills were strongly associated with a rapid rate of cognitive decline in DLB but not AD (p < .001). No effect of confrontation naming was found. DLB patients with poor visuospatial skills had fewer neurofibrillary tangles and were more likely to experience visual hallucinations than those with better visuospatial skills. These results suggest that the severity of visuospatial deficits in DLB may identify those facing a particularly malignant disease course and may designate individuals whose clinical syndrome is impacted more by Lewy body formation than AD pathology.